Ultrasonography as a Diagnostic Tool in the Management of Oro-Facial Space Infections in Pregnant Patients: A Clinical Study - Ahmad, Irshad; Shah, Masroor Khurshied (Asian Journal of Medical Research, 2022)
Background: Oro-facial space infections represent a significant amount of the dental problems in pregnant patients that present to hospital. Determining whether an odontogenic swelling is a cellulitis or abscess is difficult, but important as both may require different treatments. The use of an ultrasound may aid in differentiating cellulitis and abscess in Pregnant patients. This study was done to compare the accuracy of clinical examination alone versus ultrasonography (USG) in the diagnosis of cellulitis and abscess in symptomatic Pregnant patients with a diagnosis of superficial facial space infection: Subjects and Methods: Twenty Pregnant patients diagnosed as superficial facial space infections by clinical and radiographic examinations were included in the study. The provisional clinical diagnosis was made after a thorough history was taken and clinical examination was performed to determine if the swelling was a cellulitis or abscess. Swelling was then evaluated using the ultrasonic transducer which was placed over the swelling to aid the diagnosis which was again recorded. An incision and drainage procedure was performed after the administration of local anesthesia. The success of the ultrasound intervention versus clinical examination was based on whether frank exudation was detected during incision and drainage of such swellings. Results: The statistical analysis found that USG is a valuable diagnostic aid for detection of abscess or cellulitis in oro- facial space infections. Interpretation and Conclusion: The findings of this prospective analysis indicate that there was statistical difference between clinical examination alone and USG in making the correct diagnosis in pregnant patients. From the results of this study, ultrasound is recommended as an adjunct to clinical examination in differentiating between cellulitis and abscess.